Verapamil Inhibits Platelet Aggregation by a Calcium-Independent Mechanism - Bonadonna, Giovanni; Lechi, Clara; Corradini, Paola; Sinigaglia, Daniela; De Togni, Piero; Miroslawa, Grzeskowiak (Thrombosis and Haemostasis, 1986)
We studied the inhibitory effects of the calcium channel blocker verapamil both on platelet aggregation and intracellular calcium [Ca2+]i in platelets loaded with a fluorescent indicator (quin 2).The inhibitory effects of verapamil on the platelet aggregation response to both thrombin and ionomycin were seen to be clearly dissociated from the verapamil-induced inhibition of the [Ca2+]i increase produced by these agonists. Verapamil-induced inhibition of platelet aggregation was also obtained when using the “calcium-independent” agonist phorbol-myristate acetate (PMA). It may be deduced that a calcium-independent mechanism plays a role in verapamil-induced inhibition of platelet aggregation. We postulate that this mechanism may operate via a protein-kinase C pathway.
Keywords: Verapamil; Intracellular calcium; Platelet aggregation; Thrombin; Ionomycin